The term independent of x in the expansion of [(x + 1) / (x2/3 - x1/3 + 1) - (x - 1) / (x - x1/2)]10, x ≠ 1, is equal to

Solution:

Answer: (210)

[(x1/3 + 1) – [√x + 1] / [√x]]10 = (x1/3 – x)10

General term, Tr+1 = 10Cr (x1/3)10-r (- x)r

For term independent of x

[10 – r] / 3 – (r / 2) = 0

20 – 2r – 3r = 0

r = 4

Therefore required term, T5 = 10C4 = [10 * 9 * 8 * 7] / [4 * 3 * 2 * 1] = 210

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

Ask
Question